2015
DOI: 10.7863/ultra.14.11051
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lung Ultrasound to Assess the Efficacy of an Alveolar Recruitment Maneuver in Rabbits With Acute Respiratory Distress Syndrome

Abstract: Objectives To investigate the application of lung ultrasound (US) in the evaluation and implementation of alveolar recruitment maneuvers in acute respiratory distress syndrome (ARDS). Methods Twelve rabbits with saline lavage–induced lung injury were randomly divided into 2 groups: one with alveolar recruitment guided by lung US and the other with alveolar recruitment guided by maximal oxygenation. Recruitment maneuvers were applied according to a stepwise incremental positive end‐expiratory pressure method in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 18 publications
5
32
0
1
Order By: Relevance
“…The LUS has been used for similar indications previously also by various authors in different case reports and observational studies but with a heterogeneity in methodological approach as well as investigation used for comparison. [6710111213141516171819202122] Few studies have been described in Online supplementary material. ARDS is a condition characterized by diffuse alveolar as well as lung capillary damage, interstitial edema, and alveolar flooding leading to increased lung water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LUS has been used for similar indications previously also by various authors in different case reports and observational studies but with a heterogeneity in methodological approach as well as investigation used for comparison. [6710111213141516171819202122] Few studies have been described in Online supplementary material. ARDS is a condition characterized by diffuse alveolar as well as lung capillary damage, interstitial edema, and alveolar flooding leading to increased lung water.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Thereafter, other studies also assessed recruitment maneuver under direct guidance with bedside LUS with successful outcome. [11121314] Few studies used alternative approach to assess recruitment by LUS. [1516] Stefanidis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the lung histopathological abnormalities in rabbits with OA-induced pulmonary edema and human pulmonary edema patients are similar (Jambrik et al 2010). In addition, the lung structures of rabbits could be clearly visualized by in vivo and ex vivo lung ultrasound (Soldati et al 2014;Li et al 2015). Therefore, the present study aimed to further evaluate the value of POCUS in the assessment of the severity of pulmonary edema by analyzing the relationship between the severity of pulmonary edema and the features of BLA using a rabbit OA-induced pulmonary edema model.…”
Section: Introductionmentioning
confidence: 90%
“…In an experimental study, Li et al . [38] reported that ultrasound-guided recruitment maneuver strategy results in significant improvement of lung reaeration when compared to oxygenation-guided strategy.…”
Section: Introductionmentioning
confidence: 99%